Who's Buried in Grant's Tomb : a Tour of Presidential Gravesites. - Lamb, Brian (Perseus Books Group, 2010)
Some presidents have been larger than life but none of them have been larger than death. Brian Lamb has visited the gravesites of every American president, living and dead, in order to put together this book, with assistance from the staff of C-SPAN. Heavily illustrated and with contributions from historians Richard Norton Smith and Douglas Brinkley, Who's Buried in Grant's Tomb? is about the presidents' lives as much as it is about their final resting places. The book's collection of the presidents' last words, from Franklin Delano Roosevelt's "I have a terrific headache" to John Ad.